Penerapan Teknologi Augmented Reality sebagai Media Pembelajaran Komponen Elektronika: Mata Kuliah Elektronika Dasar - Kurniawan, Dedi; Putra, Ade (VISA: Journal of Vision and Ideas, 2024)
This study aims to apply Augmented Reality (AR) technology as a learning media for electronic components using Android. Augmented Reality technology is growing rapidly and is used in various fields such as education. By using Android devices as a platform, users can integrate Augmented Reality into applications that can be used for the introduction of electronic components, by pointing the camera to the marker in the application, augmented reality and information about the function of the electronic component will appear.  In this study, the authors used the Multimedia Development Life Cycle (MDLC) method which is a structured approach to designing, developing, and releasing creative and effective multimedia content. In the research that has been done, the results obtained are augmented reality applications for the introduction of android-based electronic components.